THE RELATIONSHIP BETWEEN KYAI, SANTRI AND PARENTS THROUGH THE “NETWORKING PACKAGE” PROGRAM IN PESANTREN - Miharja, Deni; Aripudin, Acep; Saefullah, Asep; Kholis, Nurman (State Islamic University (UIN) of Sunan Ampel Surabaya, 2026)
This article examines the adaptation of pesantren through the Networking Package program implemented at Pesantren Aljauhari, Garut, West Java. The program promotes collaboration among the kyai, santri, and parents by extending religious education into the home, thereby strengthening the integration of pesantren and family-based learning. Using a descriptive qualitative approach, this study draws on field observations, interviews, and a review of relevant literature to analyze the program’s management and educational practices. The findings indicate that the program enhances parental engagement as co-educators and reflects a broader transformation in pesantren management. Rather than relying primarily on the kyai’s personal authority, the institution adopts structured and collaborative management practices to address contemporary educational challenges. These findings demonstrate that managerial innovation can strengthen institutional sustainnability while preserving the traditional values of pesantren, providing a practical model for similar Islamic boarding schools.